Kerajinan Wayang Golek sebagai Produk Unggulan Daerah untuk Pemberdayaan Ekonomi Desa Tegalwaru - M.I. Qeis; Agung Zainal Muttakin Raden; Santi Sidhartani; Dendi Pratama (Universitas Lancang Kuning, 2019)
Tegalwaru Village has tried to develop by making itself a tourism village for Micro, Small, and Medium Enterprises (MSMEs) since 2018. However, MSMEs of Tegalwaru Village have difficulty establishing their identity in the business world due to the lack of specialty products that are unique in the market. Therefore, there is a need to innovate the regional specialty products as one of the efforts to improve the village's economy through the development of science and technology by considering the potential and uniqueness of the resources available in Tegalwaru Village. As part of the community service program, research on specialty products in this area uses qualitative methods in the form of field studies through observation and in-depth interviews. The result shows that one of the potential MSMEs of Tegalwaru Village that can be developed as a regional specialty product is Wayang Golek craft. This potential is supported by thre factors which are natural resource in the form of Pulai trees which grow around Pulekan road, human resources who have expertise in handicrafts, and the uniqueness of the product compared to the MSME around the area. However, there were major problems in the ability of MSME production and diversity of products regarding Wayang Golek in Tegalwaru Village. The implication of this study is to offer solution regarding the ability to increase MSME production and to innovate a diverse Wayang Golek product to strengthen the position of Tegalwaru Village MSMEs in market competition.